2010
DOI: 10.1002/jsfa.4020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ultrafiltration and nanofiltration of an industrial fish protein hydrolysate on its bioactive properties

Abstract: International audienceBACKGROUND: Numerous studies have demonstrated that in vitro controlled enzymatic hydrolysis of fish and shellfish proteins leads to bioactive peptides. Ultrafiltration (UF) and/or nanofiltration (NF) can be used to refine hydrolysates and also to fractionate them in order to obtain a peptide population enriched in selected sizes. This study was designed to highlight the impact of controlled UF and NF on the stability of biological activities of an industrial fish protein hydrolysate (FPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 60 publications
4
55
0
8
Order By: Relevance
“…Besides exploring diverse types of bioactivities such as ACE inhibitory activity, studies focused on the effect of oral intake in both animal and human models have revealed the excellent absorption and metabolism of isolated peptides from gelatin hydrolysates (Gómez-Guillén et al ). The enrichment of fractions or specific peptides with the aim of ultrafiltration has been widely applied in order to produce hydrolysates with improved nutritional or functional properties within specific molecular weight ranges from high molecular mass residues (Harnedy and Fitzgerald 2012;Picot et al 2010). Alcalase manifested extensive proteolytic activity during the hydrolysis of skin gelatin from Alaska pollack, squid Todarodes pacificus and giant squid, producing hydrolysates with low average molecular weight which exhibited high ACE inhibitory capacity (Giménez et al 2009;Nam et al 2008).…”
Section: Degree Of Hydrolysis (%)mentioning
confidence: 99%
“…Besides exploring diverse types of bioactivities such as ACE inhibitory activity, studies focused on the effect of oral intake in both animal and human models have revealed the excellent absorption and metabolism of isolated peptides from gelatin hydrolysates (Gómez-Guillén et al ). The enrichment of fractions or specific peptides with the aim of ultrafiltration has been widely applied in order to produce hydrolysates with improved nutritional or functional properties within specific molecular weight ranges from high molecular mass residues (Harnedy and Fitzgerald 2012;Picot et al 2010). Alcalase manifested extensive proteolytic activity during the hydrolysis of skin gelatin from Alaska pollack, squid Todarodes pacificus and giant squid, producing hydrolysates with low average molecular weight which exhibited high ACE inhibitory capacity (Giménez et al 2009;Nam et al 2008).…”
Section: Degree Of Hydrolysis (%)mentioning
confidence: 99%
“…Los cuales dependiendo de su composición, secuencia y número de aminoácidos (generalmente entre 2 -20), pueden poseer actividades biológicas, como: antihipertensiva, antioxidante, inmunomoduladora, antitrombótica, anticancerígena, entre otras (Lee et al, 2010;Picot et al, 2010;Wang et al, 2013;Deraz, 2014;Shahidi y Ambigaipalan, 2015). Diferentes investigaciones, han establecido la relación existente entre la actividad biológica de los péptidos y su peso molecular (Bourseau et al, 2009;Picot et al, 2010;Saidi et al, 2013;Wang et al, 2013;Liu et al, 2014). En particular, las fracciones de péptidos con pesos moleculares entre 1-4kDa, serían los más interesantes para usos nutricionales y/o farmacéuticos (Saidi et al, 2014;de Castro y Sato, 2015;Opheim et al, 2015).…”
Section: Introductionunclassified
“…Ultrafiltrasi menggunakan membran molecular weight cut off (MWCO) memungkinkan untuk memekatkan peptida dengan berat molekul tertentu dengan menghilangkan konsentrasi garam dan kontaminan (Vandanjon et al, 2007), sehingga aktivitasnya meningkat. Menurut Picot et al (2010), fraksinasi peptida menggunakan membran MWCO merupakan cara yang efektif untuk memekatkan peptida antioksidan, tetapi dalam prosesnya masih memerlukan optimasi. Selektivitas membran yang digunakan bukan hanya memisahkan peptida berdasarkan ukuran tetapi juga berdasarkan gugus aromatik (Picot et al, 2010) dan muatan (Doyen et al, 2011) yang berpengaruh pada bioaktivitasnya.…”
Section: Aktivitas Antioksidanunclassified
“…Menurut Picot et al (2010), fraksinasi peptida menggunakan membran MWCO merupakan cara yang efektif untuk memekatkan peptida antioksidan, tetapi dalam prosesnya masih memerlukan optimasi. Selektivitas membran yang digunakan bukan hanya memisahkan peptida berdasarkan ukuran tetapi juga berdasarkan gugus aromatik (Picot et al, 2010) dan muatan (Doyen et al, 2011) yang berpengaruh pada bioaktivitasnya. Menurut Udenigwe dan Aluko (2011) (Udenigwe dan Aluko, 2011).…”
Section: Aktivitas Antioksidanunclassified